2019
DOI: 10.1186/s12882-019-1490-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of sodium/glucose cotransporter inhibition on a rat model of angiotensin II–dependent kidney damage

Abstract: Background Renal proximal tubular sodium and glucose reabsorption are regulated by the sodium-glucose cotransporter (SGLT2). Changes in this transporter can play a role in hyperglycaemia and reactive oxygen species (ROS) production. We demonstrated increased glucose absorption in proximal tubule membrane vesicles and increased expression of SGLT2 in hypertensive rats. Here we investigated Angiotensin II (Ang II) -dependent SGLT2 expression induction and the role of SGLT2 induction in the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…In this study, Losartan prevented renal damage, whereas EMPA produced a minimal protective effect. Nonetheless, EMPA attenuated oxidative stress [ 122 ]. Clinical trials have consistently shown that SGLT2i reduces BP [ 123 ].…”
Section: Role Of Sglt and Nhe1 And Nhe3 In Cardiovascular Diseasesmentioning
confidence: 99%
“…In this study, Losartan prevented renal damage, whereas EMPA produced a minimal protective effect. Nonetheless, EMPA attenuated oxidative stress [ 122 ]. Clinical trials have consistently shown that SGLT2i reduces BP [ 123 ].…”
Section: Role Of Sglt and Nhe1 And Nhe3 In Cardiovascular Diseasesmentioning
confidence: 99%
“…Our study demonstrates that treatment with Dapa (10 mg/kg/d) alleviates renal fibrosis from UUO by inhibiting necroinflammation, oxidative stress, and apoptosis. This is supported by a variety of nondiabetic CKD studies, such as adenine-induced CKD (Ali et al, 2019) and angiotensin II-dependent kidney damage (Reyes-Pardo et al, 2019). However, an interesting result was observed from subtotal (5/6) nephrectomy.…”
Section: Discussionmentioning
confidence: 70%
“…Accordingly, empagliflozin and dapagliflozin have demonstrated no effect or attenuate renal endpoints in normotensive diabetes models with features of mild-moderate kidney pathology, including db/db mice (1,16,19,38,55,58). Empagliflozin has been demonstrated to prevent development of glomerular and tubulointerstitial fibrosis, but not GFR loss, following angiotensin II infusion or 5/6 nephrectomy in non-diabetic rodents (8,44,58). While dapagliflozin showed no glomeruloprotective effect when administered one week after 5/6 nephrectomy(62), canagliflozin treatment starting one week after angiotensin II infusion has been reported to improve GFR and improve glomerulosclerosis in normoglycemic mice (34).…”
Section: Discussionmentioning
confidence: 99%